Resultados de aplicabilidad pedagógica de una investigación cognitiva en el aprendizaje del análisis matemático - Álvarez Calvo, J. A.; Panizza, Mabel (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
We rewiew some results of an investigation on the cognitive process involved in situations of mathematical learning. The issues have been selected because of their importance on the development of a didactical teaching of mathematics, centered in the characteristics of the subject learning that particular domain. Following this criterium we present the most important features and applications that can be proposed by a cognitive study of: the influence of previous naive concepts on the representation of a cognitive domain; aspects related to problem representation; and error as a diagnostic instrument.